2006
DOI: 10.1097/01.tp.0000244598.92049.dd
|View full text |Cite
|
Sign up to set email alerts
|

Homozygous Status for HLA-E*0103 Confers Protection from Acute Graft-Versus-Host Disease and Transplant-Related Mortality in HLA-Matched Sibling Hematopoietic Stem Cell Transplantation

Abstract: These data suggest that the homozygous state for HLA-E*0103 allele behaves as a protective genetic factor against aGVHD and TRM and likely contributes to improved survival in HLA-genoidentical bone marrow transplantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(50 citation statements)
references
References 33 publications
3
47
0
Order By: Relevance
“…Moreover, an association of recipient HLA-E*0103 homozygosity with improved likelihood of patient overall survival has been observed (Bogunia-Kubik et al 2009, which concurs with the results of Tamouza et al (2006) and Danzer et al (2009). They have observed that the presence of HLA-E*0103 allele in donors, either in homozygous or heterozygous state, is associated with increased survival rate expressed by decreased TRM and decreased risk of acute GvHD (Danzer et al 2009;Tamouza et al 2006). Other studies have also confirmed the anti-GvHD effect (Ludajic et al 2009).…”
Section: Potential Role Of Hla-e and Cd94/nkg2a In Transplantation Ofsupporting
confidence: 79%
See 1 more Smart Citation
“…Moreover, an association of recipient HLA-E*0103 homozygosity with improved likelihood of patient overall survival has been observed (Bogunia-Kubik et al 2009, which concurs with the results of Tamouza et al (2006) and Danzer et al (2009). They have observed that the presence of HLA-E*0103 allele in donors, either in homozygous or heterozygous state, is associated with increased survival rate expressed by decreased TRM and decreased risk of acute GvHD (Danzer et al 2009;Tamouza et al 2006). Other studies have also confirmed the anti-GvHD effect (Ludajic et al 2009).…”
Section: Potential Role Of Hla-e and Cd94/nkg2a In Transplantation Ofsupporting
confidence: 79%
“…Minor histocompatibility antigens are presented primarily by classical HLA molecules and such complexes may activate T cells. It is hypothesized that either HLA-E outcompetes classical HLA proteins in mHags binding and disrupts the classical pathway, or it binds non-standard mHags peptides that could specifically mediate graft-versus-leukemia (GvL) rather than GvHD (Tamouza et al 2006). …”
Section: Potential Role Of Hla-e and Cd94/nkg2a In Transplantation Ofmentioning
confidence: 99%
“…This further confirms the existence of weak linkage disequilibrium between the classical HLA and HLA-E loci [59]. In HLA-E-matched allogeneic HSCT, the HLA-E*01:03/01:03 homozygous genotype has a protective role since it is associated with a lower frequency of acute and chronic GvHD, and it is associated with improved overall survival compared with other HLA-E genotypes [66,67]. Therefore, lower HLA-E expression on allograft-associated with the HLA-E*01:01 homozygous state [19] may lead to complications such as GvHD because the recipient may be less capable of inhibiting immune cells through CD94/ NKG2A receptors.…”
Section: Hla-ib In Graft-versus-host Diseasesupporting
confidence: 62%
“…Therefore, HLA-E*01:03 homozygous recipients may be better graft "acceptors" than HLA-E*01:01 patients provided that the allograft is devoid of viremia. Withal, a HLA-E genotype match should be beneficial in transplantation because the HLA-E homozygous state has been shown to be associated with transplantation outcomes, especially in BMT and HSCT [59,66,67].…”
Section: Hla-ib: Role In Histocompatibilitymentioning
confidence: 99%
“…Recent reports have shown that the homozygous state for the HLA-E*0103 allele in allo-SCT recipients, which results in a higher cell surface expression of HLA-E, is associated with a lower incidence of transplant-related mortality (54) and an improved overall survival (55). These findings suggest a protective role for HLA-E against endothelial damage by NK cells.…”
Section: Discussionmentioning
confidence: 54%